Development of stable electrochemical catalysts using ordered mesoporous carbon/silicon carbide nanocomposites. (28th September 2015) - You, Dae Jong; Jin, Xing; Kim, Jin Hoe; Jin, Seon-Ah; Lee, Sungchul; Choi, Kyoung Hwan; Baek, Woon Joong; Pak, Chanho; Kim, Ji Man
Abstract A nano-composite of ordered mesoporous carbon (OMC) and silicon carbide (SiC) was investigated as a durable support for Pt nanoparticles, in order to improve the electrochemical activity and stability in oxygen reduction reaction (ORR). The OMC and OMC–SiC were synthesized via a nano-replication method, using ordered mesoporous silica as a template and 1, 10-phenanthrolline as a carbon source at temperatures of 900 and 1350, respectively. Non-porous SiC material was obtained by heat treatment at 1600 °C. The OMC–SiC composite, containing 10.3 wt% of SiC, exhibited a high surface area (568 m2/g) and well-defined mesopores (2.7 nm). Highly dispersed Pt nanoparticles were supported on both the OMC and the OMC–SiC, using a polyol method. The ORR activity and the electrochemical surface area (ECSA) of Pt/OMC, Pt/OMC–SiC and commercial Pt/C catalysts were measured using a rotating disk electrode technique with the linear sweep method, and a potential-cycling test, respectively. The Pt/OMC–SiC composite showed the highest activity as well as the highest durability for ECSA and ORR, which may be attributed to the effect of the intimate hybridization of SiC with the OMC in nanoscale. These results indicate that the OMC–SiC composite is a very promising support material for electrochemical catalysts in fuel cells.